Human Capital As a Conditioning Factor to the Convergence Process Among the Brazilian States - Elias Soukiazis; Tulio Cravo (European Regional Science Association (ERSA), 2006)
This paper examines the convergence process among the Brazilian states using different concepts of convergence and giving special attention to the role of human capital as the conditioning factor to convergence. Different measures of human capital are used in the estimation of the convergence equations and the results show that they play a significant role in explaining the improvement of the standards of living of the Brazilian population. An interesting finding is that different levels of human capital have different impacts on the growth of per capita income depending on the level of development of the Brazilian states. Lower levels of human capital explain better the convergence process among the less developed states and higher levels of human capital are more adequate for controlling differences in the "steady-states" of the more developed Brazilian regions. The impact of the intermediate levels of human capital on growth is stronger in all samples.
Keywords: 330